Exploração sexual comercial de crianças e adolescentes : o estado da arte nas produções acadêmicas em psicologia - Mello, Leonardo Cavalcante de Araújo (2010)
The Commercial Sexual Exploitation of Children and Adolescents (ESCCA) is a phenomenon that has been given priority in public policy agenda of many democratic governments of Western countries and civil sectors of society, besides the object of studies in different fields of knowledge. Psychology is among these areas and is considered one of the references in the construction of knowledge and actions to confront the phenomenon. However, the epistemological foundations of psychological science are quite different, and so, several are his speeches, knowledge produced and ways of conceiving man and the world. This is evident in the publications of psychology on ESCCA. This work aims to achieve a state of the art of psychology publication in Brazil (in the post-graduation - through theses and dissertations - and journals) on the Commercial Sexual Exploitation of Children and Adolescents. More specifically try to evidence (a) what conceptions of commercial sexual exploitation of children and adolescents the authors lists, (b) what are aimed at research and publications, (c) how the research and issues are justified, and (d) that theoretical approaches the authors are affiliated and methodological possibilities are applied to range the aim proposed in their work. In order to do so, a survey was conducted in the major index sites (eg, BVS-Psi, Capes, theses and dissertations database of university libraries) of the material, covering the period 1990 to 2007. Through research on these sites, we built a database, including information relating to the work sought from specific descriptors for studies in the area of victimization of children and adolescents, with reference to a list provided by Faleiros (2000). After reading the summary of the work, the number of recovered 25 productions was reached - including theses, dissertations and articles. For analysis of the material used in the analysis of thematic content. Two axes themes were established in order to guide the analysis: conceptual elements of commercial sexual exploitation, and theoretical and methodological strategies employed. The axes have as reference for analysis a chapter built on the concept of commercial sexual exploitation, so that all analysis is anchored on it. The analysis points to the existence, still strong, conceptual and terminological confusion about ESCCA. Few studies have not demonstrated this confusion, maintaining a consistent theoretical approach. In relation to the theoretical and methodological strategies, there is a great diversity of approaches in psychology surrounding the phenomenon of ESCCA, enriching levels of understanding and action. This diversity reflects a constitutive heterogeneity of psychological science. We emphasize the perspective of socio-historical psychology, most frequently among the publications. It is hoped that this research will help advance the qualitative approach to ESCCA, especially in the field of psychology, as well as contribute to new research in the area and construction of new means of addressing this human rights violation